Factors Influencing Islamic Wealth Management Adoption in Malaysia from Al-Syaibani, Ibn Sina, and Al-Dimasqi’s Component of Wealth Management - Nurizal Ismail (Universiti Sains Islam Malaysia, 2024)
Matric :4191035 (FEM)